Pengembangan Modul Praktik Peradilan Semu Sebagai Upaya Peningkatan Pengetahuan Dan Keterampilan Mahasiswa Pada Mata Kuliah Hukum Acara Perdata - Puspa Dianti; Kurnisar Kurnisar; Camellia Camellia; Erisa Ramona; Yesi Kumala Sari (University of Muhammadiyah Malang, 2023)
This study aims to produce a Moot Court Practice Module as an Effort to Increase Student Knowledge and Skills in Civil Procedure Law Courses. The type of research used is development research using the Borg and Gall models. The research was conducted through three stages, namely development, validation, and product trials. Data collection techniques were carried out through documentation, questionnaires, observation sheets, and tests. Based on the research that has been done, the results show that the Moot Court Practice Module developed on a contextual basis is valid, practical, and effective for use in the learning process. The Moot Court Practice Module was declared valid with an assessment from linguists of 87.5%. Furthermore, this module was also stated to be practical as indicated by the percentage of the assessment questionnaire given by students at the third trial stage, namely 95.4%. Furthermore, textbooks were also stated to be effectively used in the learning process. This can be seen from the increase in the average posttest percentage given to students after using the module in the learning process